2010
DOI: 10.4236/as.2010.13017
|View full text |Cite
|
Sign up to set email alerts
|

Yield enhancement of droughted wheat by film antitranspirant application: rationale and evidence

Abstract: Extensive research in the 20 th century explored the potential for mitigation of drought by applying polymers (film antitranspirants) to leaves to reduce water loss. It was concluded that film antitranspirants are of limited usefulness, since the polymers reduced photosynthesis (in addition to transpiration) and this was assumed to be detrimental to growth and yield. We propose, however, that irrespective of reduced assimilate availability from photosynthesis, the most drought sensitive stage of yield formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Similarly, reduced yield from the application of AT under WW conditions was expected, since the AT film decreases leaf permeability to carbon dioxide exchange thus decreasing the supply of assimilates available for developing floret growth (Das and Raghavendra, 1979;Davenport et al, 1974;Gale and Hagan, 1966). The significantly higher grain yield observed in this study after AT application to WD plants just before booting (Z39) supports our study hypothesis and the field studies reported by Kettlewell et al (2010) on the effects of AT on yield in wheat.…”
Section: At Application Maintained Higher Grain Number Per Spike and supporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, reduced yield from the application of AT under WW conditions was expected, since the AT film decreases leaf permeability to carbon dioxide exchange thus decreasing the supply of assimilates available for developing floret growth (Das and Raghavendra, 1979;Davenport et al, 1974;Gale and Hagan, 1966). The significantly higher grain yield observed in this study after AT application to WD plants just before booting (Z39) supports our study hypothesis and the field studies reported by Kettlewell et al (2010) on the effects of AT on yield in wheat.…”
Section: At Application Maintained Higher Grain Number Per Spike and supporting
confidence: 92%
“…A broader approach has been suggested, since photosynthesis and yield not only depend on crop physiology but also on the interaction with crop developmental stages (Kettlewell, 2014;Kettlewell et al, 2010) and ambient CO 2 levels (del Amor et al, 2010). Wheat is most sensitive to drought during booting, which coincides with meiosis of pollen mother cells (Saini and Westgate, 1999;Sheoran and Saini, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data in Table ( for SPAD chlorophyll at stem elongation, booting and ear emergence, respectively. The application of antitranspirant immediately prior to booting stage may conserve water and improve grain set which could outweigh the photosynthetic limitations (14). Regarding to the reduction percentage of SPAD chlorophyll under water stress, the maximum reduction was found at Tombari and Ksar-Megrine under control treatments at stem elongation, booting and ear emergence growth stages, respectively.…”
Section: Results and Discussion 1-chlorophyll Contentmentioning
confidence: 97%
“…2A). A previous study showed that the application of an antitranspirant restricted P n and decreased plant yield (Kettlewell et al, 2010). In contrast, kaolin, a film antitranspirant, reduced P n , but provided a notable yield increase (Cantore et al, 2009).…”
Section: Discussionmentioning
confidence: 96%